CALCULATIONS OF (,n) REACTION CROSS SECTION AND GAMMA RAY INCINERATION FOR MEDIUM MASS RADIOACTIVE ISOTOPES - Al-Bayati, Abdul-Hussain; Kamoon, Saeed; Saeed, Muna (Iraqi Journal of Science, 2024)
The total -n reaction cross section for radioactive fission products have beenevaluated in the region of energy near the giant dipole resonance, from the thresholdenergy up to around 30 MeV. The selected fission products lay in the range ofmedium mass number, namely: 87Rb, 90Sr, 93Zr, 106Ru, 123Sn, 127Te, 129I and 137Cs.These radioactive isotopes were chosen as part of the radioactive waste from 235Ufission. Total cross section results were used to calculate the number of incineratednuclei, and this method shows efficiency in reducing the radioactivity of theseisotopes. The obtained results show that the incineration rate of radioactive nucleiincreases with the flux of the incident -rays, whereas the required irradiation timewas found to be shortened and inversely proportional to the incident -ray flux.These results are consistent with those given by earlier researches.